Context and the leadership experience and perceptions of professionals: a review of the nursing profession - Jefferson, Therese; Klass, Des; Lord, Linley; Nowak, Margaret; Thomas, Gail (Emerald Group Publishing Ltd, 2014)
Purpose: Leadership studies which focus on categorising leadership styles have been critiqued for failure to consider the lived experience of leadership. The purpose of this paper is to use the framework of Jepson’s model of contextual dynamics to explore whether this framework assists understanding of the “how and why” of lived leadership experience within the nursing profession. Design/methodology/approach: Themes for a purposeful literature search and review, having regard to the Jepson model, are drawn from the contemporary and dynamic context of nursing. Government reports, coupled with preliminary interviews with a nurse leadership team, guided selection of contextual issues. Findings: The contextual interactions arising from managerialism, existing hierarchical models of leadership and increasing knowledge work provided insights into leadership experience in nursing, in the contexts of professional identity and changing educational and generational profiles of nurses. The authors conclude that employing a contextual frame provides insights in studying leadership experience. The author propose additions to the cultural and institutional dimensions of Jepson’s model.Practical implications: The findings have implications for structuring and communicating key roles and policies relevant to nursing leadership. These include the need to: address perceptions around the legitimacy of current nursing leaders to provide clinical leadership; modify hierarchical models of nursing leadership; address implications of the role of the knowledge workers. Originality/value: Observing nursing leadership through the lens of Jepson’s model of contextual dynamics confirms that this is an important way of exploring how leadership is enacted. The authors found, however, the model also provided a useful frame for considering the experience and understanding of leadership by those to be led.